Life in Kings: reshaping the royal story in the Hebrew Bible - Auld, A. Graeme (Ancient Israel and its literature, 2017)
"Building on a lifetime of research and writing, A. Graeme Auld examines passages in Samuel, Kings, Chronicles, and Isaiah that recount the same stories or contain similar vocabulary. He advances his argument that Samuel and Kings were organic developments from a deftly crafted, prophetically interpreted, shared narrative he calls the Book of Two Houses--a work focused on the house of David and the house of Yahweh in Jerusalem. At the end of the study he reconstructs the synoptic material within Kings in Hebrew with an English translation"--